Current drivers, challenges and trends of infrastructure asset management - Alegre, H. (2009)
Urban water infrastructures provide essential services to modern societies and represent a major portion of the value of municipal physical assets. Managing these assets rationally is therefore fundamental for the sustainability of the services and for the economy of societies. “Asset Management” (AM) is a modern term for an old practice – assets have always been managed. In recent years, significant evolution occurred in terms of the AM formal approaches, of the monitoring and decision support tools and of the implementation success cases. However, a long way is still to go. This paper presents the highlights of key recent developments in IAM main asset management , with an emphasis on the on-going Portuguese project AWARE-P. The paper also provides an overview, inevitably subjective, of the current drivers, challenges and trends of infrastructure asset management, at an international level. It finishes with some basic guidance on how to implement an infrastructure asset management approach and with some concluding remarks.